PENGARUH PENGAWASAN TERHADAP LOYALITAS DOSEN JURUSAN ADMINISTRASI NIAGA POLITEKNIK NEGERI AMBON - Rio F. Pelupessy; Elsina Huberta Aponno; August Johannes Ufie (P3M Politeknik Negeri Ambon, 2022)
An initial survey at the Department of Commerce Administration at the Ambon State Polytechnic showed that therewere indications of problems with supervision from the leadership and loyalty of lecturers. This study aims to determine how the influence of supervision on the loyalty of lecturers at the Department of Commerce Administration, Ambon State Polytechnic.The analytical method used in this research is descriptive analysis and simple linear regression analysis. Descriptive analysis shows that supervision at the Department of Commerce Administration at Ambon State Polytechnic has an average value of 3.91 which is interpreted well, while lecturer loyalty has an average value of 4.32 which is interpreted very well. The results of the regression analysis show that supervision has a positive but not significant effect on lecturer loyalty at the Department of Commerce Administration, Ambon State Polytechnic.Based on these results, it can be concluded that the better the supervision, the better the loyalty of the lecturers. To improve it, the Department of Commerce Administration at the Ambon State Polytechnic must strive to improve supervision by paying attention to determining implementation measures, taking corrective actions and providing assessments. Lecturer loyalty can be maintained and even improved by paying attention to indicators of responsibility, obedience and obedience, honesty, and work attitude. Keywords: Supervision, Loyalty